Choroidal hemangioma in Sturge Weber syndrome: Case series with confirmed tissue diagnosis. (December 2021) - Helmi, Hala A.; Alkatan, Hind M.; Al-Essa, Rakan S.; Aljudi, Talal W.; Maktabi, Azza M.Y.; Eberhart, Charles G.
Abstract: Introduction: Sturge-weber syndrome (SWS) is a rare condition that presents with a typical facial port-wine stain, neurological manifestations such as seizures, and ocular involvement by glaucoma and/or choroidal hemangioma. In this series we demonstrate the histopathological details of the primary ocular involvement as well as the late blinding secondary ocular changes. Presentation of cases: Seven cases were included with the diagnosis of choroidal hemangioma in association with SWS (6 enucleations and one evisceration). Male to female ratio was 4:3. Age at enucleation/evisceration ranged from 25 to 68 years with a median of 42 years. Five cases had history of glaucoma (71.4%). Diffuse hemangioma was found in all (4 cavernous and 3 mixed cavernous/capillary type). Conjunctival and episcleral hemangiomas were found in 3/7. Iris neovascularization and retinal detachment were confirmed in 5/7 cases each (71%). Discussion: Our demographic and histopathological findings parallel what was previously concluded in the literature about the lack of gender predilection in SWS, and the most common ocular presentations of glaucoma and choroidal hemangioma, which is mostly diffuse in nature. The hemangioma type was found to be mostly cavernous followed by mixed capillary and cavernous. We demonstrated late associated ocular changes such as cataract, iris neovascularization, exudative retinal detachment, retinal pigment epithelium hyperplasia/metaplasia, and optic nerve atrophy, all of which aid in the poor visual outcome in these patients. Conclusion: Sturge-weber syndrome is a rare but visually disabling disease due to the associated ocular manifestations of glaucoma and choroidal hemangioma. Multidisciplinary approach because of the diverse presentation of this condition by pediatrician, neurologist, and ophthalmologist is essential with an attempt to preserve vision. Highlights: Sturge-weber syndrome (SWS) is a rare, condition manifesting with port-wine stains, seizures, glaucoma, and hemangiomas. Diffuse choroidal hemangioma (DCH) is the typical ocular lesion in SWS. We report 7 cases with histologically confirmed SWS-associated DCHs and their relevant visually disabling complications. Early diagnosis and treatment are essential for improved visual outcome.